Blocking calcium-MYC regulatory axis inhibits early dedifferentiation of chondrocytes and contributes to cartilage regeneration - Xu Wu; Yaoyao Fu; Jing Ma; Honglei Wang; Chenlong Li; Yaying Zhu; Qixuan Wang; Xudong Guo; Tianyu Zhang; Aijuan He (Stem Cell Research & Therapy)
Abstract Tissue engineering technology for cartilage regeneration has increasingly emerged as a preferred method for repairing cartilage defects. However, the loss of chondrocyte-specific phenotypes during in vitro expansion, commonly referred to as dedifferentiation, impedes cartilage regeneration. Current research has yet to fully elucidate this phenomenon, hindering the development of improved cartilage regeneration. Our study employed single-cell sequencing and transposase-accessible chromatin sequencing to identify biomarkers, cell lineages and cellular characteristics within auricular chondrocytes during in vitro expansion. Our results showed that lower passage (P3) chondrocytes exhibited more dedifferentiated phenotypes with increased chromatin accessibility, while higher passage (P6) chondrocytes demonstrated hypertrophic characteristics. Furthermore, we identified that increased calcium influx was closely associated with the early dedifferentiation of chondrocytes, while inhibiting calcium signaling in early dedifferentiated cell could reverse cell phenotypes and promoted cartilage regeneration. In-depth mechanism research revealed that the expression of MYC mRNA was downregulated by increased calcium influx, which subsequently reduced SOX5/SOX6 levels, important transcription factors for chondrocytes, leading to diminished extracellular matrix production and early dedifferentiation. In conclusion, we provide a comprehensive understanding of chondrocyte dedifferentiation and propose new strategies for optimizing cartilage regeneration systems. Graphical abstract